Influência do etanol na secagem convectiva de fatias de caqui giombo - Bianchetti, Laís Gava (2019)
Persimmons (Diospyros kaki L.) is a climacteric fruit that ripens and softens in a very short time, resulting in a gelatinous pulp. In this state, it is very vulnerable to physical and microbiological deterioration and therefore cannot be stored for a long period of time. The drying processes appear as methods to conserve and increase the shelf life and to provide the consumer with an alternative to fresh fruit in the off-season. Convective drying allows great stability of the final product, but undesirable modifications such as non-enzymatic browning, low rehydration characteristics and losses of thermosensitive nutrients may occur during processing. It is necessary to improve and apply pre-treatments in order to reverse these changes. Ethanol has been studied as a pretreatment, in order to accelerate the evaporation of water, and optimize the process time. The objective of this work was to analyze the influence of ethanol on the convective drying of Giombo persimmons slices. Pretreatment (immersion for 10 s) was performed with ethanol at concentrations of 95%, 70% and 50% ethanol. Drying without pre-treatment was also performed. Drying was conduct ed in a wind tunnel dryer at 50° and 70°C and air velocity of 1.5 m / s. The influence of pretreatment with ethanol was investigated with respect to drying time and pulp color. The kinetics of drying was adjusted with models from the literature. The empirical models of Page e Midilli et al. provided the best adjustments of the drying curves. Treatment with ethanol accelerated drying processes by up to 25%. Regarding the coloration, the fruits did not present significant differences before and after drying, without causing negative impact on the final product. In the rehydration tests, a high initial rate followed by slower absorption was observed for all treatments. Among the samples, greater rehydration was observed in slices treated with 70% ethanol at 50 ° C and without pretreatment at 70 ° C.